2020
DOI: 10.1073/pnas.1919690117
|View full text |Cite
|
Sign up to set email alerts
|

Selective reactivation of STING signaling to target Merkel cell carcinoma

Abstract: Merkel cell carcinoma (MCC) is a lethal skin cancer that metastasizes rapidly. Few effective treatments are available for patients with metastatic MCC. Poor intratumoral T cell infiltration and activation are major barriers that prevent MCC eradication by the immune system. However, the mechanisms that drive the immunologically restrictive tumor microenvironment remain poorly understood. In this study, we discovered that the innate immune regulator stimulator of IFN genes (STING) is completely silenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 71 publications
(75 reference statements)
3
77
0
Order By: Relevance
“…Several experimental studies have reported the expression of cGAS and/or STING in human melanoma, colorectal cancer, Merkel cell carcinoma, and ovarian cancer ( Xia et al, 2016a , b ; de Queiroz et al, 2019 ; Liu et al, 2020 ). However, their expression in other human cancer cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have reported the expression of cGAS and/or STING in human melanoma, colorectal cancer, Merkel cell carcinoma, and ovarian cancer ( Xia et al, 2016a , b ; de Queiroz et al, 2019 ; Liu et al, 2020 ). However, their expression in other human cancer cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…STING protein was undetectable in VP MKL-1, MKL-2 and MS-1 cells, but not in non-classical VN MCC13, MCC26 and UISO cells. Five MCC tumors (virus state not mentioned) also stained negative with STING antibodies [ 215 ]. STING silencing may help MCC tumor cells to escape immune eradication.…”
Section: Immune Evasion Of Vp-mccmentioning
confidence: 99%
“…Whether VN- and VP-MCC patients display different sensitivity to radiation is not known, but a previous study had shown that absence of STING impaired radiation-mediated tumor regression [ 220 ]. Because it was recently reported that STING expression is downregulated in VP-MCC cells [ 215 ], VP-MCC may be less sensitive to radiotherapy than VN-MCC.…”
Section: Immune Evasion Of Vp-mccmentioning
confidence: 99%
See 2 more Smart Citations